PENGARUH SHOLAT TAHAJUD TERHADAP DEPRESI PADA SANTRI DI PESANTREN AN-NUR 2 BULULAWANG MALANG - Esti Widiani; Doddy Indrawan (Care : Jurnal Ilmiah Ilmu Kesehatan, 2014)
Depression is a problem that is associated with the natural feeling. Depression should be handled appropriately and accurately so as to provide healing benefits. Tahajud prayers, prayers are held in the evening is very beneficial for the body. The purpose of this study was to analyze the influence of depression on praying tahajjud on students in pesantren An-Nur 2 Bululawang Malang. This research design using pre experimental design approach one group pre test post test design. Sampling was done by purposive sampling as many as 6 people. Analysis of the data used is the Wilcoxon test with α = 0.05. Levels of depression before treatment as much as 17% of respondents experiencing severe levels of depression and very heavy, and as much as 66% of respondents experienced moderate depression. Given the results obtained after treatment by 17% of respondents experiencing severe levels of depression, depression levels as much as 66% lighter and 33% of respondents did not have depression. From the analysis results obtained p-value of 0.027